Strategi Bisnis dalam Menghadapi Persaingan Data Center Pasca Pandemi di Indonesia (Studi Kasus: PT. XYZ Medan) - Rosadi, Arief Fareza; Wibowo, Rulianda Purnomo; Sembiring, Meilita Tryana (Universitas Batanghari Jambi, 2024)
This research aims to determine the internal and external factors in the PT XYZ Medan data center, so as to obtain the right alternative business strategy by knowing the current position of the PT the best center in Indonesia. Data was collected through interviews with top management of PT XYZ Medan. The method used is the IFE Matrix, EFE Matrix, IE Matrix, SWOT and QSPM Matrix to determine appropriate alternative data center business strategies. The results of the research show that the company's main strength factor is the data center which has the best level of security and has been certified by ISO 27001:2013 ISMS (Information Security Management System). Apart from that, the results of the IE matrix show that the position of the PT XYZ Medan Data Center is in quadrant I, namely Growth (concentration through vertical integration) and the best strategy obtained is optimizing service, quality and affordable prices in order to retain customers.